Validation and psychometric properties of the Italian version of the Power Behavioural System Scale (PBSS) - Sara Salzano; Isa Zappullo; Vincenzo Paolo Senese; Massimiliano Conson; Carmela Finelli; Mario Mikulincer; Phillip R. Shaver (Research in Psychotherapy, 2023)
The power behavioural system is a neurobehavioral system that motivates a person to acquire and control resources that are important for survival and reproductive success. When activated, its function is to protect or restore the sense of power, influence, or dominance. Repeated experiences of failure in achieving this goal may result in hyperactivation or deactivation of power-oriented behaviours (analogous to the secondary strategies observed with respect to the attachment behavioural system). Gaining a reliable and valid measure of hyperactivation and deactivation of the power system can be important for understanding an individual’s responses to different social contexts and, in clinical settings, can help the therapist identify the client’s difficulties that may undermine the therapeutic process. In the present study, we developed the Italian version of the Power Behavioural System Scale (PBSS), a self-report measure developed by Shaver et al. (2011) to assess individual differences in hyperactivation and deactivation of the power system. Results indicated an adequate fit to the expected two-factor model, and the measure proved to be reliable and had good convergent and structural validity, allowing the quantification of individual differences in power system hyperactivation and deactivation.